Hypnagogia, psychedelics, and sensory deprivation: the mythic structure of dream-like experiences - Huber, Andreas; Kjellgren, Anette; Passie, Torsten (Frontiers in Psychology, 2025)
IntroductionDream-like and psychedelic experiences often display internally illogical structures. Recent theories propose that these experiences function as “spontaneous offline simulations” related to specific brain processes. This study investigates whether such perceived illogicality reflects a distinct, premodern mode of cognition—commonly referred to as “mythic” cognition—rather than a cognitive deficit.MethodsThirty-one participants underwent four 90-minute flotation REST (Restricted Environmental Stimulation Technique) sessions designed to induce altered, dream-like states. After each session, participants completed the Phenomenology of Consciousness Inventory (PCI) and additional questions targeting features associated with mythic cognition.ResultsParticipants showed significant phenomenological shifts toward experiences characteristic of mythic cognition. Specifically, their altered states during flotation exhibited ontological parallels with mythic conceptions of space, time, and substance.DiscussionThe findings support the hypothesis that the perceived illogicality in altered states arises from a distinct cognitive framework rather than from deficits.